High risk (B3) breast lesions: What is the incidence of malignancy for individual lesion subtypes? A systematic review and meta-analysis. Issue 4 (April 2019) - Forester, Nerys Dawn; Lowes, Simon; Mitchell, Elizabeth; Twiddy, Maureen
Abstract: Introduction: Provide evidence to support evolving management strategies for high-risk (B3) breast lesions by assessing risk of carcinoma in subgroups of B3 lesions using systematic review and meta-analysis. Methods: Databases identified observational studies between 1980 and 2015 that reported on underestimation of malignancy following B3 lesion diagnosis at core needle biopsy. Critical appraisal, quality assessment, data extraction and meta-analysis was undertaken to calculate rate of malignancy of the whole B3 group and individual lesions. Study heterogeneity and association between variables and underestimation rate was investigated using random effects logistic modelling. Results: Meta-analysis, using data from 129 studies, assessed 11 423 lesions of which 2160 were upgraded to malignancy after surgical excision biopsy (17% malignancy rate, 95% CI 15–19%). Malignancy rates varied from 6% in radial scars with no atypia (95% CI 2–13%, I2 72.8%), to 32% in papillomas with atypia (95% CI 23–41%, I2 57.4%). Differences in upgrade rates between atypical and non-atypical lesions were statistically significant (p < 0.05). Study heterogeneity could not be explained by differences in core biopsy size or year of publication. Conclusions: This comprehensive, inclusive assessment of all published literature, provides an accurate estimate of malignancy risk in subgroups of B3 lesions, to guide tailored management strategies. Some lesions have a high risk of malignancy, while others have a much lower risk, and could be safely managed with surveillance strategies rather than surgery.